Work Engagement and Emotional Intelligence on Personnel Performance: The Mediating Role of Job Satisfaction - Jufrizen Jufrizen; Hazmanan Khair; Fint Boy Loviky (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Purpose – This study aims to test and analyze the effect of work engagement and emotional intelligence on personnel performance through job satisfaction directly or indirectly.Methodology – The approach used in this research is causal. The population in this study were all personnel of the Medan City Police Resort Detective section. This study used a saturated sample of 98 people, all personnel of the Medan City Police Resort Detective Section. Data collection techniques in this study using documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis using SEM-PLS using the PLS (Partial Least Square) 4.0 software program.Findings – The results of this study indicate that directly, work engagement, emotional intelligence, and job satisfaction have a significant effect on personnel performance, work engagement, and emotional intelligence have a significant impact on personnel job satisfaction, and indirectly, work attention and emotional intelligence have a significant effect on personnel performance through job satisfaction.Originality/Novelty – Combining two main concepts, namely work engagement and emotional intelligence, in one research model can provide a deeper understanding of the complexity of the relationship between the variables of work engagement, emotional intelligence, job satisfaction and employee performance.Implications – Provides valuable insights for Human Resources Management (HRM) practitioners about the importance of work engagement and emotional intelligence in improving employee performance. HRM can use these findings to develop more effective recruitment, training, and development strategies.